Data from: Development, validation, and evaluation of an assay for the detection of wood frogs (Rana sylvatica) in environmental DNA - Spangler, Mark A.; Huettmann, Falk; Herriott, Ian C.; López, J. Andrés (2017)
We developed and describe a qPCR assay for the detection of wood frogs (Rana sylvatica) using environmental DNA (eDNA) sampling. A single primer set was designed to amplify a 115-bp region of the wood frog cytochrome B gene and assessed for target specificity. There was no evidence of amplification in 11 non-target species. We evaluated the utility of the primer set in qPCR assay by conducting geo-referenced eDNA field surveys in Interior Alaska. Results indicate that the assay consistently detects wood frog DNA in the environment to 1.83 × 10−3 pg/μL. The assay provides a complement to traditional survey methods and can be readily applied in a wider conservation and management context. Wood Frog eDNA Survey Results1 liter water samples collected around Fairbanks/North Pole for eDNA analysis. Filters were cut in half and DNA isolated via phenol-chloroform from one half. Other half is archived. qPCR (SYBR Green) conducted for detection of wood frog cytB (Rasy_00).Spangler_eDNA2015.csv